Creative and critical projects in classroom music fifty years of sound and silence - Finney, John, 1944-; Philpott, Chris, 1956-; Spruce, Gary (Abingdon, Oxon ; New York, NY : Routledge, 2020)
Creative and Critical Projects in Classroom Music is both a celebration and extension of John Paynter and Peter Aston's groundbreaking work on creative classroom music, Sound and Silence, first published in 1970. Building on the central themes of the original work - the child as artist, the role of musical imagination and creativity, and the process of making music - the authors and contributors provide a contemporary response to the spirit and style of Sound and Silence. They offer reflections on the ideas and convictions underpinning Paynter and Aston's work in light of scholarship developed during the intervening years. This critical work is accompanied by16 creative classroom projects designed and enacted by contemporary practitioners, raising questions about the nature and function of music in education and society. In summary, this book aims to: Celebrate seminal work on musical creativity in the classroom. Promote the integration of practical, critical and analytical writing and thinking around this key theme for music education. Contribute to initiating the next 50 years of thought in relation to music creativity in the classroom. Offering a unique combination of critical scholarship and practical application, and published on the occasion of the 50th anniversary of Sound and Silence, themes from Paynter and Aston's work are here given fresh context that aims to inspire a new generation of innovative classroom practice and to challenge current ways of thinking about the music classroom.
Chapter 2.2 Conceptions of the creative process in music and arts education -- Introduction -- The creative process and music education -- The subjective creative process -- The conservationist creative process -- The cognitive creative process -- The virtuosic creative process -- Summary of the types -- A Type 5 -- Conclusion -- References -- Chapter 2.3 Giving value to musical creativity -- Creative teaching and learning -- What does valuing young people's musical creativity entail? -- The current climate of accountability in classroom education -- Musical assessment -- Conclusion
OCLC-licensed vendor bibliographic record.
Keywords: School music -- Instruction and study -- Outlines, syllabi, etc; MUSIC / Instruction & Study / General